Analisis Aspek-aspek Keunggulan Bersaing di Sekolah Dasar Swasta Nugraha Bandung - Sir Kalifatullah Ermaya (Coopetition : Jurnal Ilmiah Manajemen, 2020)
This study is entitled "Analysis of Competitive Advantage Aspects at SDS Nugraha, Bandung". The writing of this research is motivated by the demand for quality educational institutions that will be able to create Schools that have Competitive Advantages. This research uses a descriptive method with a qualitative approach. Respondents consisted of the Principal, Deputy Principal, teachers, and also staff in SDS Nugraha Bandung. The results showed that SDS Nugraha, Bandung already had advantages in the areas of strategic location, the breadth of the curriculum used, the program of collaboration with outsiders, adequate qualifications and quality of teachers, and also student achievement. For all this, SDS Nugraha will always continue to improve its capabilities so that schools can have a sustainable competitive advantage.